Relationship of IL-1 and TNF-alpha polymorphisms with Helicobacter pylori in gastric diseases in a Brazilian population - Santos, J. C.; Ladeira, M. S. P. [UNESP]; Pedrazzoli, J.; Ribeiro, M. L. (Associação Brasileira de Divulgação Científica (ABRADIC), 2012)
It is well known that the risk of development of gastric cancer (GC) in Helicobacter pylori-infected patients depends on several factors. Thus, the aim of this study was to investigate the effect of proinflammatory cytokine gene polymorphisms for IL-1 beta, IL-1RN and TNF-alpha on the development of GC in a Brazilian population. A total of 202 biopsies obtained from Brazilian patients with chronic gastritis and GC were included in the study. Infection with H. pylori cagA(+) was determined by the polymerase chain reaction (PCR) as previously described. IL-1 beta, IL-1RN and TNF-alpha polymorphism genotyping was performed by restriction fragment length polymorphism PCR. Associations between gene polymorphisms, clinical diseases and virulence markers were evaluated using either the chi(2) test or the Fisher exact test. Our results demonstrated that the IL-1 beta -511 C/C and IL-1 beta -511 C/T alleles were associated with chronic gastritis in H. pylori-positive patients (P = 0.04 and P = 0.05, respectively) and the IL-1 beta -511 C/C genotype was associated with GC (P = 0.03). The frequency of IL-1RN alleles from patients with chronic gastritis and GC indicated that there was no difference between the genotypes of the groups studied. Similar results were found for TNF-alpha -308 gene polymorphisms. Our results indicate that the IL-1 beta -511 C/C and C/T gene polymorphisms are associated with chronic gastritis and GC development in H. pylori-infected individuals.
Keywords: Chronic gastritis; Gastric cancer; Polymorphisms; Helicobacter pylori; Interleukins; IL-1 beta; IL-1RN; TNF-alpha